Genetic bottleneck effect and analysis of intra-population genetic diversity in Gaddi goat breed of Western Himalayas using microsatellite markers - Singh, S Gurdeep; Thakur, YP; Taggar, RK; Amitoz Kaur; Chakraborty, Dibyendu; Dhirender Kumar; Sankhyan, Varun (Journal of Livestock Biodiversity, 2025)
Genetic characterization of Gaddi goat breed was carried out with the objective to study the Bottleneck and genetic variability in the existing population. A reliable approach to measure the genetic distance between and within animal genetic resources is to estimate the difference in the frequencies of different genetic variants (alleles) at a number of marker loci. The breeds that share same alleles at similar frequencies are genetically closely related, whereas those having the same alleles at different frequencies or different allele's altogether are further apart. The variability within a breed can also be estimated by examining the number and frequency of alleles. In the present study, microsatellite markers based molecular genetic characterization of “Gaddi”, a goat breed native to north temperate western Himalayan region of India, was carried out to analyze existing intra population diversity. The multi-locus genotype data was generated on 51 Gaddi goats sampled across different locations of  the breeding tract in Himachal Pradesh using 15 FAO recommended goat specific microsatellite markers, which gave amplification and observed and effective number of alleles, gene frequency, observed and expected heterozygosity were estimated. The screened loci were not found to be in accordance  with  Hardy  Weinberg  equilibrium  for  several  microsatellite  frequencies  except  INRABERN172  and MAF065. The overall mean FIS (0.102 ± 0.02) ranged between -0.1406 (INRABERN-172) to 0.2527 (SPS113). The overall mean FIS (0.102) observed in the present study indicated a 10.2 percent shortfall of heterozygosity in the population studied. The Ewens-Watterson test for neutrality indicated that observed F value of for 11 microsatellite loci except four (MAF70, ILSTS029, P19 (DYA) and SPS113) lied within the lower and upper boundaries of the 95% confidence region for expected F. The qualitative graphical method was employed to visualize the allele frequency spectra. The mode shift analysis revealed L-shaped curve confirming that the population had not experienced genetic bottleneck effect in recent past and is in mutation-drift equilibrium.